A possible representation of Yin Yang five elements (Yin Yang Wu Xing): Hypothesis of Dual Five-Body-Coordination - Hwe Ik Zhang (Integrative Medicine Research)
Background: The idea of Yin Yang Wu Xing, traditionally adopted and practiced in East-Asian medicine, has not been incorporated into the theoretical framework of modern medicine. It is therefore desired to show that Yin Yang Wu Xing is a manifestation of a higher-level faculty of cooperating system, thus making it suitable for a modern frame of thought. Methods: A higher-level faculty of the cooperating system is formulated in the scheme of Dual Five-Body Coordination. The stability of this scheme is examined mathematically and the feasibility of its physical realization is estimated. Results: The Dual Five-Body Coordination scheme, which overlaps substantially with the conceptual structure of Yin Yang Wu Xing, is stable and has survival merit. An imaginable conjecture based on physical reality confirms its physical feasibility. Conclusion: The Dual Five-Body Coordination scheme has potential utilization in various fields including biology and sociology. Once the theoretical framework is solidified, the Dual Five-Body Coordination scheme can be readily applied in practical research in modern medicine.